Rare Earth-Doped SrTio3 Perovskite Formation from Xerogels. (14th November 2012) - Rocca, Anastasia; Licciulli, Antonio; Politi, Monia; Diso, Daniela
Abstract : A synthesis process of rare earth doped SrTiO3 by modified sol-gel technique is described. Impervious strontium titanate doped with rare earth was prepared by gelification and calcination of colloidal systems. Powders of thulium substituted strontium titanate (SrTi 1 - x Tm x O 3 - δ, where x = 0.005 ; 0.02; 0.05) were obtained through cohydrolysis of titanium, strontium, and thulium precursors by sol-gel method. The xerogel obtained from the evaporation of solvents was milled and calcinated at 1100°C to give a reactive powder. Pure and doped SrTiO3 dense disks were formed by uniaxial pressing. Thermogravimetry (TGA), differential scanning calorimetry (DSC) analysis, X-ray diffractometry (XRD), and scanning electron microscopy (SEM) have been used to study the microstructural evolution of amorphous xerogel into crystalline reactive and sinterable powders. Hardness was measured for each membrane by a Vickers microindenter. Dilatometric and TGA-DSC in pure CO2 flow tests have been performed to evaluate, respectively, the thermal and chemical stability of the material. The optimized preparation route has allowed to synthesize highly reactive easy sintering powders used for fully densified, impervious ceramics with high thermal and chemical stability at high temperature.